The Depiction of Various Crimes in Shaukat Siddiqui’s Novel "Jangloos". - Imtsal Arshad; Dr. Mamuna Subhani (Zaban-o-Adab, 2022)
Shaukat Siddiqui’s novel Jangloos gives a clear and powerful picture of crime and corruption in Pakistan’s social and political system after partition. The story takes place in both villages and cities that shows the difficulties faced by poor and oppressed people as they fight against injustice. The characters in the novel—ranging from farmers and thieves to corrupt landowners and politicians—are involved in different types of crimes, such as stealing, murder, land grabbing, and exploiting the weak. The beauty of this novel is that it fits in current situation of Pakistan as well.